Modelización de la calidad del agua del estero El Limón, cantón Quevedo, provinci de Los Ríos, estación lluviosa, año 2018 - 2019 - Pérez Párraga, Maybe Liliana (2019)
The purpose of the water quality models is to generate information on the behavior of water sources, and to predict their future scenarios, this research was carried out in the El Limón stream, belonging to the Quevedo Canton province of Los Ríos in the months of the rainy season February, March and April, in order to model the quality of their water, evaluating the dissolved oxygen (DO) and biochemical oxygen demand (BOD) concentrations in the estuary, for which the following objectives were met: proposed: (1) determine the hydromorphological characteristics of the estuary, (2) characterize the water quality of the El Limón estuary, (3) model the water quality with the Streeter-Phelps model, and, (4) simulate water quality with the QUAL2K software. The characterization was carried out through the physical-chemical parameters that were: dissolved oxygen (DO), biochemical oxygen demand (BOD), temperature (° C), hydrogen potential (pH), and electrical conductivity (EC) in the nine ten samples, which were: upstream, section 1, section 2, section 3, section 4, one discharge and four tributary streams. The calibration and modeling was carried out through the mathematical expressions of the Streeter-Phelps model. To calibrate the model, the kinetic constants of deoxygenation (Kd), reaayation (Ka) and total removal of the BOD (Kr) were adjusted. , using the Generalized Likelihood Uncertainty Estimation (GLUE) methodology, using statistical software Statgraphics using the Monte Carlo simulation tool. Finally, the QUAL2K program was used to carry out the simulation of water quality, making use of the data taken in the estuary and the calibrated constants. Keywords: Water quality, Dissolved oxygen, Biochemical Oxygen Demand, Streeter- Phelps, Qual2k, Calibration, Validation, GLUE methodology, Monte Carlo algorith